A Child Presenting with Persistent Asymptomatic Microscopic Hematuria: a Case Report - Naghshizadian, Rama (Journal of Pediatric Nephrology, 2019)
Tuberculosis (TB) is a serious and important infectious disease worldwide. Children commonly develop renal tuberculosis (TB) as a complication of primary pulmonary infection with Mycobacterium tuberculosis characterized by hilar lymphadenopathy often with lung opacity. Renal TB accounts for up to 27% of extra-pulmonary cases. The disease is more prevalent in children with immunodeficiency syndromes and the recipients of organ transplantations. The signs and symptoms of renal TB are non-specific and challenging. Most patients present with persistent non-glomerular microscopic hematuria without abdominal or flank pain. Some may have signs and symptoms of the lower urinary tract such as voiding dysfunction. A diagnosis of renal TB is suspected upon detecting pyuria in the absence of common bacterial infections and is confirmed by isolation of acid-fast lactobacillus in the urine or tissue biopsy. Anti-tuberculosis drugs most frequently used in the pediatric age group are a combination of isoniazid, rifampicin, pyrazinamide, and ethambutol. Keywords: Non-glomerular hematuria; Renal tuberculosis; Diagnosis; Treatment; Child; Mycobacterium tuberculosis.